Slow light nanocoatings for ultrashort pulse compression - M. Ossiander (Nature Portfolio, 2021)
Controlling the dispersion of femtosecond light pulses remains a key challenge for their application. Here, the authors report dispersion-engineered transmissive nanocoatings for ultrashort laser pulse compression in the vis-NIR spectral region.